Malignant Pineal Parenchymal Tumors in Adults: A National Cancer Database Analysis. Issue 6 (23rd June 2022) - Chalif, Eric J.; Murray, Richard D.; Mozaffari, Khashayar; Chillakuru, Yeshwant R.; Shim, Timothy; Monfared, Ashkan; Sherman, Jonathan H.
Abstract : BACKGROUND: Limited retrospective data exist on malignant pineal parenchymal tumors (PPTs) in adults, and there are no large previous studies that review clinical outcomes across the 3 treatment arms of surgery, radiotherapy, and chemotherapy. As a result, optimal disease management has yet to be defined. OBJECTIVE: To evaluate treatment trends and perform survival analysis in adult PPT. METHODS: The National Cancer Database was queried for histologically confirmed PPT diagnosed from 2007 to 2016. Univariate and multivariate Cox regressions were used to evaluate the prognostic impact of covariates. Kaplan–Meier survival curves were generated for comparative subanalyses. RESULTS: Of the 251 patients who met inclusion criteria, 172 had PPTs of intermediate differentiation (PPTID) and 79 had pineoblastoma. A plurality of patients with pineoblastoma were treated with trimodal therapy (39.1%), whereas patients with PPTID were commonly treated with either surgery alone or surgery and radiation (33.7% each). Factors independently associated with improved overall survival include younger patient age, female sex, lower comorbidity score, lower tumor grade, and treatment with surgery or radiation (each P < .05). Subanalyses confirm the effect of radiation on survival in patients with grade III PPTID with subtotal resection; however, no survival benefit of adjuvant radiation is demonstrated in patients with grade II PPTID with subtotal resection. CONCLUSION: Although radiotherapy and surgery were found to increase survival in all patients with PPT, there was no demonstrable survival benefit of adjuvant radiation in surgically treated patients with grade II PPTID. This suggests that adjuvant radiotherapy may not add significant survival benefit in many adult patients with grade II PPTID. Abstract :